PROSHADE – Tietoon pohjautuva jaettu päätöksenteko terveydenhuollossa - Rosenlund, Milla; Jylhä, Virpi; Vahteristo, Anna; Turja, Tuuli; Kuusisto, Hanna (Finnish Journal of eHealth and eWelfare, 2023)
The PROSHADE project is funded by the Strategic Research Council of the Academy of Finland for 2021–2026. The project is part of LITERACY program, where interdisciplinary solutions are researched and searched on critical information usage of individuals and organizations. In PROSHADE the focus of research is on decision-making and utilization of information in healthcare. PROSHADE consists of four work packages (WP). This presentation focuses on work package 3 (WP3), which researches health information literacy and the participation of patients in shared decision-making in healthcare. Increasing patient's participation according to earlier studies leads for example to better treatment success, patient satisfaction and stronger commitment to treatment. Patient’s health literacy (the ability to identify, search, evaluate, and generate health-related data) plays a central role in shared decision-making. Patient generated data enables patient’s values and preferences to be taken into account better as part of shared decision-making. However, research is required to further strengthen shared decision making in interactions in healthcare.